MECHANISATION OF MEDIUM SOIL PLOUGHING ON FLAT TERRAIN 30 CM DEEP IN THE SOIL - Anișoara DUMA COPCEA; Radu ILEA; Casiana MIHUȚ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper presents the mechanisation technology of medium soil ploughing 30 cm deep in the soil given that the ploughing area is 100 ha (1000 m x 1000 m) and that the ploughing aggregate is made up of a Deutz Fahr 150 tractor and a LemkenEuropal – 4 reversible born plough. After choosing the movement direction, we identify the turning areas at the ends of the plot. At the beginning, the turning area is market by poles, and then we plough 6-8 cm deep. These marks point to the transport and working position of the plough. The turning areas are worked after the plot is ploughed.